2023
DOI: 10.18280/jesa.560206
|View full text |Cite
|
Sign up to set email alerts
|

A Supply Chain Inventory Model for a Deteriorating Material under a Finite Planning Horizon with the Carbon Tax and Shortage in All Cycles

Abstract: We have framed an inventory replenishment model under a finite planning horizon in which replenishment cycle time and replenishment cycle length are different and don't repeat. The finite planning horizon for different replenishment times and cycle lengths is a real-life scenario. Nowadays, every manufacturing industry wants to achieve maximum profit at a low cost. It is very difficult to maintain the optimal level of inventory, total cost, replenishment time, and replenishment cycle. Along with the health of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In the realm of Blockchain-based dynamics, recent studies such as [6][7][8] has shown that the real-time assessment of retailer demand depends on instantaneous stock levels. This complex relationship is expressed through the demand rate equation…”
Section: Defining the Model Mathematicallymentioning
confidence: 99%
See 1 more Smart Citation
“…In the realm of Blockchain-based dynamics, recent studies such as [6][7][8] has shown that the real-time assessment of retailer demand depends on instantaneous stock levels. This complex relationship is expressed through the demand rate equation…”
Section: Defining the Model Mathematicallymentioning
confidence: 99%
“…In addition, this study incorporates quantitative analysis by employing numerical examples extracted from a secondary dataset compiled from a diverse array of [6,7]. Our analysis is firmly grounded in a robust foundation.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies can validate theoretical findings, and policy evaluations can guide stakeholders. Additionally, extending the analysis to include two-and three-echelon supply chains, and holds promise for deeper understanding and practical relevance [23,24]. By using preposition and Eq.…”
Section: Ordered Quantity and No Of Replenishment Cycles With Changin...mentioning
confidence: 99%
“…Since 𝑡 𝑛 1 =H-𝑇 𝑛 1 Following the studies [21,24], we also employed the concept of mathematical induction to establish that 𝑇 𝑖 increase with the 𝑇 𝑛 1 =n-1, n-2……….2.1 Put i=𝑛 1 -1 When we put i=n 1-1 into Eq. (10), we obtain:…”
Section: Appendix Amentioning
confidence: 99%